2017
DOI: 10.1017/s0007123417000242
|View full text |Cite
|
Sign up to set email alerts
|

How do Economic Circumstances Determine Preferences? Evidence from Long-run Panel Data

Abstract: Preferences for redistribution and social spending are correlated with income and unemployment risk, but it is unclear how these relationships come about. I build a theory emphasizing that only large changes in economic circumstances provide the information and motivation needed for people to change their preferences. Stable long-run preferences are shaped mainly by early socialization, which includes economic and ideological influences from the family, and early labor market experiences. Enduring shocks, low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 62 publications
5
44
0
3
Order By: Relevance
“…In sum, the findings presented here provide strong support for our expectations that women from pink‐collar backgrounds advance different legislative preferences and priorities than (1) white‐collar women, (2) blue‐collar men, and even (3) pink‐collar men. We provide support for the theories that class (Carnes 2013, 2012; Micozzi 2018; O'Grady 2017) and gender (Kreitzer 2015; Osborn 2012) are central to the policymaking process. By integrating these bodies of scholarship, we demonstrate that working‐class women are uniquely situated to advocate for education and social services policies.…”
Section: Other Factors Explaining Spendingsupporting
confidence: 53%
See 1 more Smart Citation
“…In sum, the findings presented here provide strong support for our expectations that women from pink‐collar backgrounds advance different legislative preferences and priorities than (1) white‐collar women, (2) blue‐collar men, and even (3) pink‐collar men. We provide support for the theories that class (Carnes 2013, 2012; Micozzi 2018; O'Grady 2017) and gender (Kreitzer 2015; Osborn 2012) are central to the policymaking process. By integrating these bodies of scholarship, we demonstrate that working‐class women are uniquely situated to advocate for education and social services policies.…”
Section: Other Factors Explaining Spendingsupporting
confidence: 53%
“…Members of the working class are descriptively underrepresented in political office (Carnes 2018). When present, representatives with working-class backgrounds shape policy outcomes, including supporting workers and labor policy (Carnes 2013;Carnes and Lupu 2015;O'grady 2017). at the same time, the representation of women in political office has been shown to shape policy outcomes in profound ways, such as budget allocation and spending on women's issues (Clayton and Zetterberg 2018;Funk and Philips 2019;Holman 2014Holman , 2015.…”
mentioning
confidence: 99%
“…The formative years between childhood and adulthood are considered especially important in these respects (Neundorf & Smets, 2017, p. 4). A recent British Household Panel Study (BHPS) analysis has found intergenerational transmission of both parents’ ideologies, as well as persistent effects of growing up in poverty (O’Grady, 2019). As current class is associated with class origins, class differences in socialization and early experiences have a potentially confounding impact on contemporary attitude differences between classes.…”
Section: Methodsmentioning
confidence: 99%
“…The straightforward self-interest expectation is that people will support LMPs more strongly after their employment situation deteriorates. Similarly, their support for LMPs will decrease after their employment situation improves (Margalit 2013;O'Grady 2019). In contrast, the 'values perspective' emphasizes predispositional, and thus attitudinal, stability.…”
Section: Values Versus Self-interest and Beyondmentioning
confidence: 98%